2023
DOI: 10.1007/s00705-023-05770-1
|View full text |Cite|
|
Sign up to set email alerts
|

Repurposing of artesunate, an antimalarial drug, as a potential inhibitor of hepatitis E virus

Abstract: Hepatitis E virus (HEV) is endemic in several developing countries of Africa and Asia. It mainly causes self-limiting waterborne infections, in either sporadic or outbreak form. Recently, HEV was shown to cause chronic infections in immunosuppressed individuals. Ribavirin and interferon, the current off-label treatment options for hepatitis E, have several side effects. Hence, there is a need for new drugs. We evaluated the antimalarial drug artesunate (ART) against genotype 1 HEV (HEV-1) and HEV-3 using a vir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 92 publications
0
5
0
Order By: Relevance
“…The use of ribavirin is contraindicated in pregnancy; however, its use in HEV-ACLF is worth testing in selected cases. There have been attempts to evaluate alternative drugs in treating difficult patients with HEV-gt3 chronic hepatitis [152]. Inhibits replication in vitro A clinical trial demonstrated that sofosbuvir was not effective on HEV [153] The role is unclear.…”
Section: Hev Rna (Nat)mentioning
confidence: 99%
See 2 more Smart Citations
“…The use of ribavirin is contraindicated in pregnancy; however, its use in HEV-ACLF is worth testing in selected cases. There have been attempts to evaluate alternative drugs in treating difficult patients with HEV-gt3 chronic hepatitis [152]. Inhibits replication in vitro A clinical trial demonstrated that sofosbuvir was not effective on HEV [153] The role is unclear.…”
Section: Hev Rna (Nat)mentioning
confidence: 99%
“…Hepatitis E ORF2 expression, self-assembly, and virus-like particles with native HEV (T = 3) and assembled VLP (T = 1). HEV ORF2 proteins with different lengths have been expressed and purified in several systems in order to determine their particle-forming properties [152]. The native HEV particles have 660 aa with T = 3 icosahedral symmetry and 180 units of the ORF2 protein encircling HEV RNA [100].…”
Section: Hev Rna (Nat)mentioning
confidence: 99%
See 1 more Smart Citation
“…This substance, however, will require additional validation by in vivo testing in animal models and pharmacokinetic/pharmacodynamic investigations [128]. A recent study [129] showed that the antimalarial Artesunate was able to inhibit HEV replication by directly blocking both the helicase and the RNA-dependent RNA polymerase. A further element of interest about this drug is represented by the fact that it is safe in pregnant women, who are well-known high-risk individuals.…”
Section: Therapeutic Options For Hev Infectionmentioning
confidence: 99%
“…Non-pregnant patients with chronic HEV infection were shown to benefit from a 12-week course of ribavirin (RBV) monotherapy [ 111 ]. RBV is a guanosine nucleoside analog that acts as a viral polymerase inhibitor, and it has been usually given to solid organ transplant recipients in conjunction with immunosuppressive therapy reduction [ 114 , 115 , 116 , 117 , 118 , 119 , 120 , 121 , 122 , 123 , 124 , 125 , 126 , 127 , 128 , 129 ]. Table 1 contains details about the described drugs and their mechanisms of action in immunocompromised patients.…”
Section: Virologymentioning
confidence: 99%